Порівняльна характеристика спрощеного судочинства у США та окремих європейських країн - Власова, А.; Vlasova, A. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті автор зазначає, що процедури спрощеного судочинства активно застосовуються провідними зарубіжними країнами. Зокрема, у США поширеною є практика укладання угоди про визнання вини. В змісті наукової статті автор аналізує законодавство та приходить до висновку, що в європейських країнах правові системи зближуються й інститут визнання вини поступово набуває актуальності. При розкритті змісту спрощеного судочинства автор констатує, що законодавство Італії передбачає дві відповідні процедури, а саме, прискорене провадження та укладання угоди про визнання вини. У висновках наукової статті автор пропонує деякі правові норми щодо угоди про визнання вини, яка складає основу спрощеного провадження у США, імплементувати в національне законодавство України. The article discusses the features and procedure for entering into a plea agreement in the United States and some European countries, the need to implement good practices in Ukraine. The author notes that the summary proceedings procedure is widely used by leading foreign countries. In particular, in the United States generally accepted plea bargain. Their essence lies in the fact that the criminal procedure law of that country provides for the possibility of a kind of «trade» between the prosecutor and the defendant, who with the consent of the prosecutor is entitled to plead guilty to a less serious offense than that specified in the indictment or accusation statement. This is a special agreement between the prosecution and defense, according to which the prosecutor is required to qualify as a less serious offense, and the accused must plead guilty. In the scientific article, the author concludes that in European countries, despite the differences in legal systems, the institute «recognition» is becoming urgent. United Nations Economic and Social Council adopted a Resolution about the basic principles of restorative justice programs in criminal procedure from 24 July 2002 y. The author notes that Italian law provides for two procedures, namely the accelerated production and the conclusion of the plea agreement. In conclusions of the scientific article the author offers some legal provisions of the plea agreement, which is the basis of summary proceedings in the United States to implement the national legislation of Ukraine. This will simplify the procedure for dealing with certain categories of criminal cases, will help shorten the duration of the detention, procedural time limits for consideration of criminal cases and save budgetary costs of criminal justice, as well as reduce the burden on the investigative and judicial systems.
Comparative Characteristics of Summary Proceedings in United States and Some European Countries.
Keywords: угода про визнання вини; спрощене судочинство; правовий компроміс; прискорене провадження; plead guilty; summary proceedings; legal compromise; accelerated proceedings